Implementation of Islamic Religious Education in Developing Students' Religious Character - Yuliharti (GoAcademica Research & Publishing, 2022)
Education must be oriented to cultivate religious individuals who possess religious ideals. Before learning many other topics, an educational institution should present and instill monotheism or faith in its students as the fundamental foundation. This study aimed to determine the process of implementing Islamic religious education in SD IT Miftahul Iman Pekanbaru to instill religious values in students. This is a field study employing a qualitative descriptive methodology. The findings of this study indicate that the implementation of Islamic religious education in building religious values at IT Miftahul Iman Elementary School Pekanbaru is carried out well and effectively by implementing it in daily activities such as getting used to saying greetings, shaking hands, being polite in speaking, being polite in attitude, and having mutual respect for both teachers and peers. In addition, student-centered extracurricular learning activities are conducted with an emphasis on conceptual and illustrative content and contextual examples.